2016
DOI: 10.1016/j.jtusci.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of photocatalytic decolourization of cationic dye using porous TiO2 film

Abstract: In this work, the kinetics of the photocatalytic decolourization of methylene blue (MB) is investigated using different surface morphologies of multilayer TiO 2 coating onto a glass plate under irradiation from a 55-W household florescent lamp. A simple direct dip-coating technique was used, and the coating properties of TiO 2 powder were improved by adding epoxidized natural rubber (ENR) as an organic binder in the coating formulation. The effects of the fundamental parameters that govern the kinetics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(59 citation statements)
references
References 23 publications
1
57
0
1
Order By: Relevance
“…Since the degradation processes studied in this work are surface phenomena the textural parameters are key factors for promoting the contact between the TiO2 and the involved molecules [52][53][54][55]. A high surface area promotes the degradation processes [54,[56][57][58] and the pore volume allows the molecule diffusion to activate photocatalyst sites through the pore structure [28,53,59,60]. Successively, nitrogen physisorption tests were carried out in order to evaluate the texture of these composites.…”
Section: Sol-gel Characterizationmentioning
confidence: 99%
“…Since the degradation processes studied in this work are surface phenomena the textural parameters are key factors for promoting the contact between the TiO2 and the involved molecules [52][53][54][55]. A high surface area promotes the degradation processes [54,[56][57][58] and the pore volume allows the molecule diffusion to activate photocatalyst sites through the pore structure [28,53,59,60]. Successively, nitrogen physisorption tests were carried out in order to evaluate the texture of these composites.…”
Section: Sol-gel Characterizationmentioning
confidence: 99%
“…Hence, a pH value lower that 6.5 will cause a poor degradation of MB dye, and this explains the gap in photocatalytic degradation rate obtained beyond pH 6.5 seen in Figure 5b. However, the photoactivity efficiency decreased at pH 12 to become 0.062 min −1 due to the rapid adsorption of dye which covered the photocatalyst surface, thus resulting in a slower photocatalytic activity [35]. Nonetheless, the removal rate of MB by TiO 2 /PEG film was largely attributed to adsorption, since the visible blue-stained surface indicated that the film was not fully photocatalytically degraded.…”
Section: Effects Of Phmentioning
confidence: 99%
“…This model depends on sorption equilibrium capacity and can be identified as 28 t/q t = (1/k 2 q e 2 )+ t/q e (6) where k 2 is the second-order reaction rate equilibrium constant (g mg -1 min -1…”
Section: Pseudo Second-order Rate Modelmentioning
confidence: 99%
“…Therefore, the environmental protection agencies call it as mandatory to treat dye bath effluents prior to discharging them into the surrounding aquatic systems or planning any reuse 4 . Coloured effluents contaminated with dyes are usually treated with several physicochemical de-colourization processes, such as coagulation, precipitation, ozonation, photo-catalysis 5,6 , irradiation, and filtration 7 . Among these technologies, none has appeared as a panacea owing to high costs, low efficiency, and limited versatility 8 .…”
Section: Introductionmentioning
confidence: 99%